DNAJC13 p.Asn855Ser mutation screening in Parkinson's disease and pathologically confirmed Lewy body disease patients. (September 2015) - Lorenzo‐Betancor, O.; Ogaki, K.; Soto‐Ortolaza, A. I.; Labbe, C.; Walton, R. L.; Strongosky, A. J.; van Gerpen, J. A.; Uitti, R. J.; McLean, P. J.; Springer, W.; Siuda, J.; Opala, G.; et al.
<x xml:space="preserve">Abstract</x> Background Recently, a novel mutation in exon 24 of DNAJC13 gene (p.Asn855Ser, rs387907571) has been reported to cause autosomal dominant Parkinson's disease (PD) in a multi‐incident Mennonite family. Methods In the present study the mutation containing exon of the DNAJC13 gene has been sequenced in a Caucasian series consisting of 1938 patients with clinical PD and 838 with pathologically diagnosed Lewy body disease (LBD). Results Our sequence analysis did not identify any coding variants in exon 24 of DNAJC13. Two previously described variants in intron 23 (rs200204728 and rs2369796) were observed. Conclusion Our results indicate that the region surrounding the DNAJC13 p.Asn855Ser substitution is highly conserved and mutations in this exon are not a common cause of PD or LBD among Caucasian populations.